Feasibility of Biology Teaching Materials for Class X SMA - Aisyah, Nur (RADINKA JAYA UTAMA PUBLISHER, 2024)
Teaching materials in general are things that contain information and knowledge that can be learned by their users. In learning activities, teaching materials act as a medium that mediates the process of conveying knowledge and skills from the resource person to the person learning. This type of research is both descriptive and qualitative. The qualitative descriptive approach method is a data processing method that analyzes factors related to the research object by presenting data in more depth regarding the research object. The data obtained from interviews with informants was described thoroughly. From the results of the interviews that have been conducted, it can be concluded that the teaching materials used by teachers are quite good, but there is still a lack of image references.